Pengaruh penggunaan tepung daun kelor (Moringa oleifera) dalam ransum terhadap kadar kolesterol dan kadar lemak dalam daging ayam broiler - Kelik Prabowo; A. Edi Widodo; Sangle Y. Randa (Cassowary, 2023)
Fat deposition in broiler chickens is generally found in the abdominal cavity and under the skin. The fat content of broiler chicken is 5.79-8.44% with a mass of fat by ±10%, higher than the fat content of local chicken, namely of 1.18-2.76%, the cholesterol content of every 100 grams of wet meat of domestic chicken is similar to that of broiler chicken, 116 mg and 110 mg, respectively. The cholesterol content of broiler stomach contents is higher than that of free-range chicken. The highest cholesterol content of broiler innards is liver (529 mg/100 g) and the lowest is heart (171 mg/100 g), while for free-range chicken the highest is the kidney (336 mg/100 g) and the lowest is the heart (164 mg). /100g). The cholesterol content of free-range chicken eggs is 922 mg/100 g, almost twice that of broiler eggs, which is 485 mg/100 g. Moringa leaves (Moringa oleifera) as a source of feed with high nutritional value also has a function to control cholesterol levels and fat levels in broiler chicken meat. The experimental design used a completely randomized design with five treatments, namely (P0). Without the addition of Moringa leaf flour (control), (P1). Addition of 4% Moringa leaf flour, (P2). Addition of Moringa Leaf Flour 8%, (P3). Addition of 12% Moringa Leaf Flour and (P4). Addition of 16% Moringa Leaf Flour. Each treatment used 3 broiler chickens aged 12 days with 4 replications. The results showed that there was a significant difference between treatments, treatments P0 and P2 had lower cholesterol levels in meat than chickens with other treatments. Fat content in meat there was a significant difference between treatments, P3, P2 and P4 had lower levels of fat in meat than chicken with other treatments.